Solvent abuse: a case report and a review - Sarvesvaran, R.; Hasnan, J. (College of Pathologists, Academy of Medicine Malaysia, 1994)
The deliberate inhalation of solvents among children and adolescents "for kicks" is becoming more common in the West. It was generally regarded as a relatively harmless practice and consequently little attention had been paid to the isolation of the toxic agent from the variety of substances used. It is now well recognised that solvent abuse not only can result in sudden death but also cause pathological changes to the liver, kidney, brain, heart and lungs. A case of toluene associated death in Malaysia is discussed both from a medico-legal and pathological standpoint.